2016
DOI: 10.1073/pnas.1606303113
|View full text |Cite
|
Sign up to set email alerts
|

Early life stages contribute strongly to local adaptation in Arabidopsis thaliana

Abstract: The magnitude and genetic basis of local adaptation is of fundamental interest in evolutionary biology. However, field experiments usually do not consider early life stages, and therefore may underestimate local adaptation and miss genetically based tradeoffs. We examined the contribution of differences in seedling establishment to adaptive differentiation and the genetic architecture of local adaptation using recombinant inbred lines (RIL) derived from a cross between two locally adapted populations (Italy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
171
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(180 citation statements)
references
References 55 publications
6
171
0
1
Order By: Relevance
“…Of course there will be further mortality in the seed bank and not all established seedlings will survive and reproduce, but the results serve to illustrate that selection on DOG1 could be very strong indeed, and lend credence to the notion that the observed distribution of dormancy and DOG1 alleles (Figures 1C and 3D) reflects local adaptation. Although our experiments have limitations and do not allow us to decompose total fitness, our results agree with those from previous studies, and it becomes very clear that germination timing is one of the main (if not the main) fitness components (Postma and Ågren, 2016; Huang et al, 2010a). To fully understand how selection acts will require multi-generational field experiments as selection pressures are likely to vary from year to year (and are unlikely to be at equilibrium, because of large-scale climate variations).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Of course there will be further mortality in the seed bank and not all established seedlings will survive and reproduce, but the results serve to illustrate that selection on DOG1 could be very strong indeed, and lend credence to the notion that the observed distribution of dormancy and DOG1 alleles (Figures 1C and 3D) reflects local adaptation. Although our experiments have limitations and do not allow us to decompose total fitness, our results agree with those from previous studies, and it becomes very clear that germination timing is one of the main (if not the main) fitness components (Postma and Ågren, 2016; Huang et al, 2010a). To fully understand how selection acts will require multi-generational field experiments as selection pressures are likely to vary from year to year (and are unlikely to be at equilibrium, because of large-scale climate variations).…”
Section: Resultssupporting
confidence: 89%
“…As a consequence, we could only estimate survival between dispersal in June and the onset of winter in November. Postma et al (2016) have shown that survival during this phase is critical to plant performance. Thus, we believe that our estimations of ‘fitness’ are realistic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reciprocal transplants have predominantly been applied for herbaceous and shrubby species growing in temperate regions (Fenster & Galloway, 2000; Franks, Weber, & Aitken, 2014; Grassein, Lavorel, & Till‐Bottraud, 2014; Malikova, Latzel, Smilauer, & Klimesova, 2016), with few exceptions in the tropics (Chen & Schemske, 2015), because it may take several years to evaluate the overall plant performance during an individual's life span. Although all the phases should be studied in order to obtain the complete picture of ecotypic adaptations, in arboreal species it may be methodologically appropriate, if not plainly inevitable, to split the cycle into practical sets of phases: As Darwin 1994, page 86, put it: “… so in a state of nature, natural selection will be enabled to act on and modify organic beings at any age, by the accumulation of profitable variations at that age, and by their inheritance at a corresponding age.” As significant plant mortality occurs during the seedling establishment and sapling growth phenophases, natural selection should in theory strongly benefit variants within plant populations with higher plant performance in these phases (Postma & Agren, 2016). Hence, plant performance during seedling establishment and sapling initial growth of long‐lived species should logically be a reliable indicator of ecotypic differentiation in the context of range size and habitat distribution.…”
Section: Introductionmentioning
confidence: 99%